Dust Source Identification in the Middle East by Using Remote Sensing - mehdi boroghani; sima pourhashemi; mohamadali zanganeh Asadi; hamidreza Moradi (مخاطرات محیط طبیعی, 2017)
A dust storm is a common phenomenon in many parts of the world, especially in arid and semiarid regions of the world. Dust storm adverse effects on the agriculture production and gardening, pollution of water and soil resources, a variety of respiratory diseases and the finally on the environmental issues, social challenges, a sharp reduction in horizontal visibility and road accidents. In this research, dust source identification in the Middle East with using MODIS satellite images was used in the period of time 2004-2014. For dust source identification 4 indices BTD3132، BTD2931، NDDI and D for 45 MODIS satellite images were calculated. Then with make a false-color combination (FCC) determined the best of a method dust source identification. The results showed that color combination BTD2931 ، B4 and B3 determined the best color combination for enhancement dust and dust source identification. The results showed that 212 points dust source identified in the case study that 123 points were in Iran and 93 Points in out of the country. The results also show that after Iran, Afghanistan has highest points dust source in the study area. The Middle East arid and semi-arid climates and precipitation in this area rarely exceed 300 mm per year As a result; this area has been poor vegetation cover and precipitation hardening and is susceptible to erosion.